Target Localization Accuracy of Image Registrations in Cone Beam Computed Tomography‐Guided Stereotactic Body Radiation Therapy for Lung Cancer - Seong Soon Jang; Na‐Young An; Hee Kyung Kim; Youngjun Yang; Gil Ja Huh; Joon Won Jeong (Thoracic Cancer)
ABSTRACT Background To evaluate the target localization accuracy of image registration methods in cone beam computed tomography (CBCT)‐based image guidance (IG) for lung stereotactic body radiation therapy (SBRT) and the associations with tumor characteristics such as size, mobility, and location. Methods Four methods involving different matching axes and regions were used to register the planning CT and 3D CBCT images of 36 lung tumors treated with SBRT. The registration axes were divided into 3D translational axes and 6D axes (translational and rotational axes), and the regions were divided into wide rectangular (WR) volume‐of‐interest (VOI) and tumor‐focused (TF) VOI, consisting of the internal target volume (ITV) plus a 1 cm margin. Results Compared with the WR registrations, the TF registrations yielded higher localization accuracies for all registration pairs, with differences of 6.3%–9.1% in the percentage of inclusion of the registered CBCT gross tumor volume (GTV) into the ITV and 1.3–1.8 mm in the 3D distance between the ITV and registered CBCT GTV centroids. The TF3D and TF6D registrations yielded similar accuracy metrics of 91.9% and 1.4 mm, respectively, whereas the WR6D registration exhibited improved accuracies compared with the WR3D registration. The localization accuracies with the TF registrations decreased with increasing tumor mobility index, expressed as the ITV/GTV50% ratio, with significant differences between the tumor groups at a cutoff of 1.7. Conclusions The localization accuracies of our image registration methods may serve as clinically useful references for selecting the most suitable registration in CBCT‐based IG for lung SBRT.